Sugar cane crops Trinidad - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
Sugar cane in bloom.
Cataloger's title
Keywords: Sugarcane -- Trinidad and Tobago; Caroni(1975)Limited